Explaining changes in the age distribution of displaced workers - Daniel Rodriguez; Madeline Zavodny (Federal Reserve Bank of Atlanta, 2000)
Using Displaced Worker Survey data, this paper examines changes in the age distribution of displaced workers during the 1983–87 and 1993–97 periods. Older workers comprised a significantly larger fraction of displaced workers during the later period. Potential explanations for this phenomenon include demographic shifts in the labor force, changes in technology, and industry and occupational shifts. Kernel density estimates indicate that the aging of the labor force accounts for the majority of the shift in the age distribution of displaced workers. Changes in technology also appear to have contributed to the shift in the age distribution of displaced workers by increasing the likelihood of displacement among older workers relative to younger workers. Differential changes across age groups between goods-producing and service-producing jobs and between blue-collar and white-collar jobs appear to have had little effect on the change in the age distribution of displaced workers.
Keywords: 330; Labor turnover; Demography; Labor supply